A first report of East Asian students' perception of progress testing: a focus group study. Issue 1 (December 2016) - Matsuyama, Yasushi; Muijtjens, Arno; Kikukawa, Makoto; Stalmeijer, Renee; Murakami, Reiko; Ishikawa, Shizukiyo; Okazaki, Hitoaki
Abstract Background Progress testing (PT) is used in Western countries to evaluate students' level of functional knowledge, and to enhance meaning-oriented and self-directed learning. However, the use of PT has not been investigated in East Asia, where reproduction-oriented and teacher-centered learning styles prevail. Here, we explored the applicability of PT by focusing on student perceptions. Methods Twenty-four students from Years 2, 3, and 5 at Jichi Medical University in Japan attended a pilot PT session preceded by a brief introduction of its concept and procedures. Variations in obtained test scores were analyzed by year, and student perceptions of PT were explored using focus groups. Results Formula scores (mean ± standard deviation) in Years 2, 3, and 5 were 12.63 ± 3.53, 35.88 ± 14.53, and 71.00 ± 18.31, respectively. Qualitative descriptive analysis of focus group data showed that students disfavored testing of medical knowledge without tangible goals, but instead favored repetitive assessment of knowledge that had been learned and was tested on a unit basis in the past in order to achieve deep learning. Further, students of all school years considered that post-test explanatory lectures by teachers were necessary. Conclusions East Asian students' perceptions indicated that, in addition to their intensive memorization within narrow test domains compartmentalized by end-of-unit tests, the concept of PT was suitable for repetitive memorization, as it helped them to integrate their knowledge and to increase their understanding. Post-test explanatory lectures might lessen their dislike of the intangible goals of PT, but at the expense of delaying the development of self-directed learning. Key issues for the optimization of PT in East Asia may include administration of PT after completed end-of-unit tests and a gradual change in feedback methodology over school years from test-oriented post-test lectures to the provision of literature references only, as a means of enhancing test self-review and self-directed learning.